Description of Cognitive Function in Diabetes Mellitus: A Literature Review - Puspasari, Susy; Andrianto, Endar (KnE Life Sciences, 2021)
Cognitive decline in diabetes mellitus is not fully understood, though is generally ascribed to blood sugar levels exceeding normal (hyperglycemia), hypoglycemia conditions and insulin resistance. Cognitive function consists of aspects of memory, attention, executive function, perception, language, and psychomotor functions which affect the decline in cognitive function, especially in people with Diabetes Mellitus. This study aims to summarize the results of research on cognitive function in people with Diabetes Mellitus. The research method used was a literature review with an assessment using JBI critical appraisal tools. Articles were sourced via the PubMed database and Google Scholar using the search term ‘Cognitive Function AND Diabetes Mellitus’. The inclusion criteria were studies with quantitative design, full text, a population comprised of patients with Diabetes Mellitus, written in Indonesian or English. Six articles were reviewed, all the results state that patients with Diabetes Mellitus experienced a decrease in cognitive function, especially in the Executive Function, Visuospatial, and the Memory Domains. Keywords: Cognitive function, Diabetes mellitus, Literature review